FACTORS AFFECTING THE PRODUCTION OF SWEET POTATOES IN SEMARANG DISTRICT - Purnomo, Trias (Efficient: Indonesian Journal of Development Economics, 2019)
The purpose of this research is: 1) To know the description of sweet potato farming in Semarang regency in economic terms. 2) To know and analyze the influence of the factors of production (land area, labor, seeds, fertilizer) to production of sweet potato in Semarang regency. 3) To know and analyze the influence of all factors of production (land area, labor, seeds, fertilizer) together to production of sweet potato in Semarang Regency. This research type is descriptive research by using quantitative approach. Independent variables in this study are land area, labor, fertilizer and seedlings. While the dependent variable is the production of sweet potato. The method of analysis used in this research is multiple regression analysis with OLS (Ordinary Least Square) method. The results of this study indicate that the variable land area has a positive and significant influence with the coefficient of 0.67. Labor variable has positive and significant influence with coefficient value of 0.28. While variable of fertilizer and seedlings do not have a significant influence on sweet potato production. Variable land area, labor, fertilizer and seedlings together have a significant influence on productivity of sweet potato in Semarang regency. Tujuan dari penelitian ini adalah: 1) Untuk mengetahui gambaran usahatani ubi jalar di Kabupaten Semarang secara ekonomi. 2) Untuk mengetahui dan menganalisis pengaruh faktor-faktor produksi (luas lahan, tenaga kerja, benih, pupuk) terhadap produksi ubi jalar di Kabupaten Semarang. 3) Untuk mengetahui dan menganalisis pengaruh semua faktor produksi (luas lahan, tenaga kerja, benih, pupuk) secara bersama-sama terhadap produksi ubi jalar di Kabupaten Semarang. Jenis penelitian ini adalah penelitian deskriptif dengan menggunakan pendekatan kuantitatif. Variabel independen dalam penelitian ini adalah luas lahan, tenaga kerja, pupuk dan bibit. Sedangkan variabel terikatnya adalah produksi ubi jalar. Metode analisis yang digunakan dalam penelitian ini adalah analisis regresi berganda dengan metode OLS (Ordinary Least Square). Hasil penelitian ini menunjukkan bahwa variabel luas lahan memiliki pengaruh positif dan signifikan dengan koefisien 0,67. Variabel tenaga kerja memiliki pengaruh positif dan signifikan dengan nilai koefisien 0,28. Sedangkan variabel pupuk dan bibit tidak memiliki pengaruh yang signifikan terhadap produksi ubi jalar. Variabel luas lahan, tenaga kerja, pupuk dan bibit secara bersama-sama memiliki pengaruh yang signifikan terhadap produktivitas ubi jalar di Kabupaten Semarang.